2016
DOI: 10.1158/0008-5472.can-15-3455
|View full text |Cite
|
Sign up to set email alerts
|

Design and Reporting of Targeted Anticancer Preclinical Studies: A Meta-Analysis of Animal Studies Investigating Sorafenib Antitumor Efficacy

Abstract: The validity of preclinical studies of candidate therapeutic agents has been questioned given their limited ability to predict their fate in clinical development, including due to design flaws and reporting bias. In this study, we examined this issue in depth by conducting a meta-analysis of animal studies investigating the efficacy of the clinically approved kinase inhibitor, sorafenib. MEDLINE, Embase, and BIOSIS databases were searched for all animal experiments testing tumor volume response to sorafenib mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 53 publications
0
13
0
2
Order By: Relevance
“…In vitro as well as in vivo experiments using sorafenib enabled us to uncover the MФ–NK cell crosstalk and identify actual response‐predicting biomarkers such as IL1B and IL18. The sorafenib‐induced immunological changes were also present at lower doses, although HCC tumor growth inhibition was dose‐dependent . Previous trials had described high variability of the sorafenib biodistribution comparing mice and humans .…”
Section: Discussionmentioning
confidence: 95%
“…In vitro as well as in vivo experiments using sorafenib enabled us to uncover the MФ–NK cell crosstalk and identify actual response‐predicting biomarkers such as IL1B and IL18. The sorafenib‐induced immunological changes were also present at lower doses, although HCC tumor growth inhibition was dose‐dependent . Previous trials had described high variability of the sorafenib biodistribution comparing mice and humans .…”
Section: Discussionmentioning
confidence: 95%
“…Better regulatory guidance on the design of preclinical efficacy studies might help reduce the burdens and costs associated with attrition during drug development. Just recently, the need for more robust study designs in preclinical efficacy studies was highlighted (Mattina et al, 2016). Regulatory guidelines could strongly support these activities (Begley and Ellis, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the particularly complicated processes involved in the occurrence and development of tumors (17,18). It may be caused by the regulation of cell growth and proliferation (19).…”
Section: Discussionmentioning
confidence: 99%